A mercury optical lattice clock at LNE-SYRTE. (June 2016) - De Sarlo, L; Favier, M; Tyumenev, R; Bize, S
Abstract: We describe the development of an optical lattice clock based on mercury and the results obtained since the 7 th SFSM. We briefly present a new solution for the cooling laser system and an improved lattice trap that allows us to interrogate a few thousand atoms in parallel. This translates into a fractional short term stability of 1.2 x 10 -15 at the clock frequency of 1.129 PHz.